Biogranulation development during treatment of real textile wastewater - Krishnen, Ranjeni (2018)
Over the past decades, effluent discharge from textile industries to neighbouring water bodies can cause severe water pollution if discharged untreated. There are quite a number of treatment systems have been invented to treat textile wastewater, but each treatment system had its own limitations. The most common limitations are low efficiency, inapplicability to treat a wide variety of dyes, production of secondary waste and high cost. Currently, biological treatment using biogranules had showed promising results in treating textile wastewater. However, most studies are being done using synthetic wastewater at lab scale reactor. This study looks at the development and application of biogranules in treating the actual textile wastewater using pilot-scale reactor. A pilot-scale Sequential Batch Reactor (SBR) biogranular system with working volume of 70 L was developed and operated according to SBR’s sequence for 24-hr cycle, which includes sequential anaerobic and aerobic reaction phases. Wastewater from two textile mills were used as feed, while sewage and pineapple wastewater were used as co-substrate. After operating the system for 60 days, 30% of the sludge transformed into biogranules and increased to 67% at the end of the study. The biogranules developed in the reactor have sizes ranging from 0.2 mm to 9.5 mm with a mean settling velocity of 28 ± 7 m/hr and Sludge Volume Index (SVI) of 73.9 mL/g. At the end of the development period, the system yields 92% removal of Chemical Oxygen Demand (COD), however color removal fluctuated throughout the development period in the range of 50 to 70%. The efficiency of biogranules in treating textile wastewater was evaluated using lab scale bioreactor with total working volume of 3L. The system was able to achieve 55% of average color removal and 88% of average COD removal at 7%v/v pineapple wastewater concentration during the treatment period. The experiment on treatment of raw textile wastewater without any added nutrient proved the importance of co-substrate in dye degradation. Conversely, the addition of external dye degrader microbes in the reactor had slightly improved color removal. The system obtained 59% of mean color removal and 81% of mean COD removal at 5%v/v pineapple wastewater concentration upon addition of dye degrader microbes into the bioreactor. Microorganisms under genus Pseudomonas, Klebsiella and Enterococcus were identified within the mature biogranules which are considered in the literature as dye degrader microbes. Although the biogranules development is much faster in lab-scale reactor under controlled environment, the findings indicate the feasibility of developing biogranules in a bigger scale reactor using actual textile wastewater and other high-strength biodegradable wastewater as co-substrate.